Edukasi Pengadopsian Perilaku Hidup Bersih dan Sehat pada Masyarakat Kumuh dan Miskin Perkotaan di Kota Serang - Vina Oktiarina; Achmad Hufad; Maman Fathurrohman; Sri Wahyuni (SAP (Susunan Artikel Pendidikan), 2023)
The environmental situation of Serang continues to degrade in quality and quantity due to the low level of awareness of the Clean and Healthy Behavior of the community. The community is still doing open defecation in an open place so that the Serang City government is pursuing the PHBS program in the form of healthy family toilet. This study aims to examine the educational model on the application of the PHBS program in the form of healthy family toilet in slums and urban poor communities in Serang City. The method used in this study is qualitative with the presentation of data in the form of a narrative. The results showed that Serang is more dominated by laggard-type people with characteristics of suspicious views and a tendency to reject all existing innovations. They are stubborn when it is recommended to change their old habits, thus making it difficult to make changes towards a better life.